REPRESENTASI BUDAYA DAYAK DAN KOMUNIKASI PARIWISATA MELALUI TIKTOK: ANALISIS SEMIOTIKA VISUAL TERHADAP VIDEO BUDAYA KALIMANTAN TENGAH - Wilantari, Ni Nyoman Ayu (Fakultas Dharma Duta, 2025)
Abstract This study explores how the culture of the Dayak people of Central Kalimantan is represented in TikTok videos produced by local creators, and how this platform functions as a medium for culture-based tourism communication. The study employs a descriptive qualitative approach and visual semiotics analysis, examining five TikTok videos that feature cultural symbols such as longhouses, traditional clothing, traditional dances, and sape music. The analysis reveals that the visual representations in these videos reflect a dynamic, participatory, and community-based construction of cultural identity. TikTok, as a visually-driven platform with popularity algorithms, enables local culture to be presented in an aesthetic, emotional, and contextual manner, reaching a broad audience across regions and generations. Presentation styles ranging from cinematic, documentary, to contemplative provide diverse narrative dimensions to cultural symbols, enriching the audience's experience. Tourism communication theory (Kotler et al., 2010) emphasizes the importance of destination branding and communication of attributes, both tangible and intangible. TikTok has proven to be an effective medium in shaping audience perceptions of local culture and tourism potential. Based on Stuart Hall's representation theory and Nicholas Mirzoeff and Malcolm Barnard's visual culture theory, this study shows that social media not only facilitates the dissemination of culture but also serves as an active space for the formation of meaning, identity, and the image of tourist destinations. TikTok can be positioned as a strategic tool in tourism communication based on local wisdom, with its visual strength and user participation as key elements in supporting cultural preservation and enhancing the sustainable appeal of destinations.